2010
DOI: 10.2500/ajra.2010.24.3549
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and Tissue Eosinophilia Correlations in Nasal Polyposis

Abstract: Nasal cytological eosinophilia is a simple, fast, nontraumatic, and inexpensive method in the evaluation of patients with nasal polyposis. Eosinophilic infiltration of the nasal mucosa is characteristic of nasal polyposis. It correlates with the stage of the disease and tends to be higher in patients with asthma, nasal polyposis, and nonsteroidal anti-inflammatory drug intolerance (acetyl-salicylic acid triad).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…Allergies have been found to predispose individuals to CRSwNP, as the symptoms of watery rhinorrhea and mucosal swelling were present in the diseases, along with an abundance of eosinophils in the nasal secretions. Some studies have shown that eosinophils are possibly the most important inflammatory cells in the pathogenesis of chronic rhinosinusitis with nasal polyposis [2,15]. Staphylococcus aureus is a common bacterial pathogen that may play an important role in the pathogenesis of CRSwNP via tissue remodeling and eosinophilic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Allergies have been found to predispose individuals to CRSwNP, as the symptoms of watery rhinorrhea and mucosal swelling were present in the diseases, along with an abundance of eosinophils in the nasal secretions. Some studies have shown that eosinophils are possibly the most important inflammatory cells in the pathogenesis of chronic rhinosinusitis with nasal polyposis [2,15]. Staphylococcus aureus is a common bacterial pathogen that may play an important role in the pathogenesis of CRSwNP via tissue remodeling and eosinophilic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CRS who demonstrate greater tissue eosinophilia have been shown to have greater disease severity and worse prognosis and quality of life after surgery . The histopathological degree of tissue eosinophilia has also been demonstrated to be higher in patients with asthma, nasal polyps, and nonsteroidal anti‐inflammatory drug intolerance . However, as noted in one study by Snidvongs et al., the authors found MEC to be a good marker for eosinophilic disease severity regardless of CRS subtype because approximately 19% of patients with eosinophilic disease presented without polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination of mucosal tissue in patients with CRS typically shows mononuclear cells as well as eosinophils . Tissue eosinophils have previously been implicated as markers of disease severity in patients with CRS, particularly in patients with nasal polyps . Prior immunohistochemical staining of sinonasal tissues for EG2, which is a marker for activated eosinophils, demonstrated all tissue with >5 eosinophils/high‐power field (Eos/HPF) stained positively, suggesting active disease at this histopathologic count .…”
mentioning
confidence: 99%
“…Most histological studies of nasal polyp have been performed in Caucasian patients and data from Asian population is still lacking. The majority was found to be eosinophil-predominant, comprising 73-92.5% (Armengot et al 2010; interleukin-8, which is an important chemo-attractant of neutrophil, and size of nasal polyps (Wen et al 2012;Majima 2004), while it showed poor therapeutic efficacy and worse clinical response in eosinophilic NP (Haruna et al 2009;Peric et al 2011). By understanding the histological types of the NP, it would provide us certain prognostic information and allow specific tailored treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies conducted on Caucasian population showed that eosinophil-predominant was the most common feature of NP and ranged between 73-92.5% of their sample size (Armengot et al 2010;Garin et al 2008;Snidvongs et al 2012;Couto et al 2008). However, research studies conducted in India and Asian countries showed that about 48-69% of NP was neutrophil predominant and had lower cases of eosinophil-predominant NP compared to the Caucasian studies (Dafale et al 2012;Hao et al 2006;Ba et al 2011).…”
Section: Introductionmentioning
confidence: 99%